2009
DOI: 10.3748/wjg.15.356
|View full text |Cite
|
Sign up to set email alerts
|

Genomic-wide analysis of lymphatic metastasis-associated genes in human hepatocellular carcinoma

Abstract: Tumor metastasis is an important biological characteristic, which involves multiple genetic changes and cumulation. This genome-wide information contributes to an improved understanding of molecular alterations during lymph node metastasis in HCC. It may help clinicians to predict metastasis of lymph nodes and assist researchers in identifying novel therapeutic targets for metastatic HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…Also our "Up in Metastatic" signature revealed elevated levels of solute carrier proteins, namely SLC25A5 and SLC25A3. The former has been implicated earlier to be elevated in lymph node metastasis associated with hepatocellular carcinoma (81), whereas SLC25A3 serves as the mitochondrial transporter for phosphate (82). Interestingly, independent metabolomics data for prostate cancer progression generated by our laboratory revealed significantly elevated levels of inorganic phosphate in tumors, corroborating with the finding of elevated levels of phosphate carrier in metastatic prostate cancer (83).…”
Section: Discussionsupporting
confidence: 79%
“…Also our "Up in Metastatic" signature revealed elevated levels of solute carrier proteins, namely SLC25A5 and SLC25A3. The former has been implicated earlier to be elevated in lymph node metastasis associated with hepatocellular carcinoma (81), whereas SLC25A3 serves as the mitochondrial transporter for phosphate (82). Interestingly, independent metabolomics data for prostate cancer progression generated by our laboratory revealed significantly elevated levels of inorganic phosphate in tumors, corroborating with the finding of elevated levels of phosphate carrier in metastatic prostate cancer (83).…”
Section: Discussionsupporting
confidence: 79%
“…Downregulation of PTPN2 has been previously shown in different types of cancer. In hepatocellular carcinoma, loss of PTPN2 was correlated with presence of lymph node metastasis [36]. PTPN2 loss through gene deletions or mutations have been reported in T-cell acute lymphoblastic leukaemia (T-ALL) and peripheral T-cell lymphoma not otherwise specified, and has been coupled to increased cytokine sensitivity and proliferation through stimulation of the Janus kinase/signal transducers and activators of transcription (JAK/STAT) -signalling pathways [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that genes favoring metastasis progression are initiated in the peritumoral liver microenvironment of HCC (9,13). Further, Lee and colleagues reported that frozen HCC tissue can provide genome-wide information that contributes to an improved understanding of molecular alterations during LNM in HCC (27). In this study, we evaluated gene expression in primary tumors and in the peritumoral liver microenvironment and identified 83 genes that were differentially expressed between the LNM and NLNM groups.…”
Section: Discussionmentioning
confidence: 99%